Perilous Intimacies: Debating Hindu-Muslim Friendship After Empire - Yohanan Friedmann (American Journal of Islam and Society, 2024)
The subtitle of the book under review suggests that it deals with modern relationships between Hindus and Muslims in India, but the scope of the book is actually much wider. It deals with the general question of the various Muslim views of the relationship between Muslims and adherents of other civilizations and religions, ranging from the 9th century al-ʿĀmirī and the 11th century al-Bīrūnī, to the 18th century Mirzā Maẓhar Jān-i Jānān and thinkers of the 19th and 20th centuries, including such luminaries as Abū al-Kalām Āzād, Aḥmad Riźā Khān, Sayyid Aḥmad Khān and several Deobandī scholars. One of the great virtues of the book is the author’s use of the sources, some of them rarely mentioned in scholarly literature and certainly not to this extent and in such detail. In an academic culture in which various “narratives” have taken the pride of place, it is most welcome to have a work which is replete with theory, but also surveys and analyzes a substantial amount of hitherto unknown source material. The book is also another proof of the great variety of Muslim tradition which enables Muslim scholars to find Islamic justification for their modern world views and policies, even if these are contradictory to each other. Because of its rich content – much of it unknown – the book deserves a detailed review.